Impact of Government Expenditure on Economic Growth in Nigeria: Implications for Policy Implementation - Chekwume Ikechukwu, Kingsley; Maku, Owen; Onoriode Ashakah, Felix (INTERNATIONAL JOURNAL OF ECONOMICS AND MANAGEMENT REVIEW, 2025)
Purpose - This study aims to assess the impact of government expenditure, specifically capital and recurrent expenditures, on economic growth in Nigeria. The objective is to determine which form of spending most effectively stimulates economic development and to offer policy guidance for optimizing fiscal resource allocation. Design/methodology/approach - The research adopts an ex-post facto design using annual time series data from 1980 to 2022. Key variables include GDP growth rate, gross capital formation, employment, inflation, government capital expenditure, and recurrent expenditure. The Autoregressive Distributed Lag (ARDL) model and Dynamic Ordinary Least Squares (DOLS) techniques were employed to examine both short-run and long-run relationships among the variables, following unit root and cointegration tests. Originality -  The study contributes uniquely to fiscal policy literature by using a dual-model estimation approach (ARDL and DOLS) to robustly evaluate Nigeria’s government expenditure effectiveness. It also focuses on the disaggregated effects of capital and recurrent expenditure in a developing economy context where such separation is often blurred in policy application. Findings and Discussion - The results show that both capital and recurrent expenditures do not have a statistically significant effect on economic growth in Nigeria during the study period. In contrast, employment demonstrates a consistent positive impact. The analysis suggests inefficiencies, poor execution of capital projects, and inadequate fiscal targeting as contributing factors to the ineffectiveness of public spending. No long-run cointegration was established, further supporting the notion of weak fiscal transmission mechanisms. Conclusion - Government expenditure in Nigeria, as currently structured, has limited effectiveness in fostering economic growth. The study recommends reforming public expenditure management, enhancing transparency and accountability, and prioritizing employment-generating projects to promote sustainable growth.